Psychosocial effects of divorce on young women who grew up in divorced families at Rustenburg, Moruleng Village - Maforah, N.F.; Matlakala, F.K.; Mohlatlole, N.E. (Technium Social Sciences Journal, 2021)
Parental divorce account for a host of emotional, behavioural, and social maladjustment in children and the phenomenon have been found to be a major risk factor for both internalizing and externalizing problems in children and young adults. Yet, limited research attention has focused on the effect of parental divorce and the psychosocial needs of children. These connections have implication for behaviour in adulthood. The present study therefore explored the psychosocial effects of divorce on young women who grew up in divorced families at Rustenburg, Moruleng Village. The study employed qualitative approach and exploratory research redesign. Sample of 5 young women from Rustenburg in Moruleng Village were sampled using snowball sampling technique and data was analysed thematically through the aid of Atlas Ti qualitative software. In this study, findings show that young women from divorced families expressed negative feelings and emotions and distorted emotions after episode of parental divorce. They further indicated that these young women in later adulthood develop and form hate characters as a result of the abusive and shock experiences during the processes of parental divorce. Based on these findings, it is recommended that government should prioritize children rights, particularly children from divorced families in South Africa and provide free counselling services for them as this will assist in decreasing negative feelings and emotions, promote positive behaviour and ensure stable adulthood behaviour.